Barriers and Supports in Empowering Parents Care for Children with Cancer - Dina Rasmita (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Cancer that occurs in children does not only affect children, but also parents. Parents experience anxiety, stress, fear of losing their children, and helplessness in caring for their children, so that parents are less than optimal in caring for their children. Parent empowerment can increase parents' knowledge, confidence, and ability to care for their children. Previous research found several obstacles to parent empowerment carried out by nurses so that parent empowerment was not optimal in its implementation. Knowing barriers and supports in implementation of parent empowerment in caring for children with cancer can support implementation of parent empowerment to be more optimal. The purpose of this study was to explore barriers and supports in parent empowerment in caring for children with cancer based on the nurse's perception. The design of this study was qualitative research design with a phenomenological approach. The data was collected by in-depth interview method using semi-structured interview guidelines on six nurses who were selected by purposive sampling technique. The data analysis was carried out by thematic analysis with the analysis stage according to Colaizzi. The results of this study were resulted in four themes, namely parental attitudes, parental characteristics, attitudes of nurses, availability of nurses and facilities. This study concluded that implementation of empowering parents to care for children with cancer became more optimal by knowing the barrier and supports in empowering parents care for children with cancer and nurses could make more effective planning in caring for children with cancer.